Investigating the potential risk of cadmium exposure on Osteoporosis: An integrated multi-omics approach - Yiwei Li; Xuezhen Liang; Yifa Rong; Kai Jiang; Jiahao Zhang; Gang Li (Ecotoxicology and Environmental Safety)
Osteoporosis (OP) is a chronic progressive bone disease, and its occurrence and development under cadmium exposure remain unclear. This study aims to explore the role of cadmium exposure in the pathogenesis of OP through a comprehensive analysis of multi-omics data. Through cross-sectional analysis using National Health and Nutrition Examination Survey (NHANES), we observed that cadmium exposure is a risk factor for OP. Bioinformatics and machine learning further emphasized the importance of FOXO3, CCND1, MAP1LC3B, HMOX1, and MT1G as independent risk factors for OP, which was confirmed through robust internal validation. Single-cell RNA sequencing revealed the heterogeneous expression of cadmium-related genes in different cell populations, with a particular emphasis on the role of HMOX1 in cell communication and signaling. Through Gene Set Enrichment Analysis (GSEA), we found that HMOX1 is positively correlated with the activity of M2 macrophage polarization. Through Mendelian randomization (MR), molecular docking, and molecular dynamics simulations, we further discovered that geniposide can target and bind to HMOX1. Ultimately, this comprehensive study elucidates the role of cadmium exposure in OP and highlights the potential of HMOX1 as a therapeutic target in alleviating the adverse effects of the disease.